MAKNA MAKIAN PADA KOMENTAR SUPORTER BONEK SURABAYA MENGENAI TAYANGAN VIDEO PERSEBAYA DI YOUTUBE - Nova Dwi Mulyani; Jailani Jailani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
Human life certainly requires other people to communicate convey the main contents of their minds. In human life can not be separated from what is called language. Language is the most important role for the lives of surrounding communities. Language can express feelings of sadness, pleasure, disappointment, anger, praise, intimacy, and hatred. On the contrary, with swear words that have feelings of irritation, anger or revenge. The method used in this study uses the referral method, record method and documentation method. This research is more likely to use qualitative and descriptive approaches. Data retrieval seen from comments from bonek surabaya fans on youtube in the form of writing. Then, see in the conversation to comment on each other's opinions. In addition, noting important parts that can indeed be examined adjusts the objectives and the data is obtained and documented into the data card based on the date, month and year for 6 months. The results of the research of the Surabaya supporters, the invective in the form of a single form has 80 percent, while the invective other than the single form is 20 percent.